Inflammation and Cardiovascular Risk: Investigating the Link between CRP and Coronary Artery Disease - Khan, Farhat Ullah; Musa, Muhammad; Bibi, Ayesha; Iqbal, Mohsin; Khan, Muhammad Idrees (Indus Journal of Bioscience Research, 2025)
Objective: To evaluate the association between C-reactive protein levels and the severity of coronary artery disease in a population of patients. Methodology: This was a retrospective observational study involving 220 patients, divided into two groups based on their hs-CRP levels: Group A (